2020
DOI: 10.18494/sam.2020.2615
|View full text |Cite
|
Sign up to set email alerts
|

Strike Activity Detection and Recognition Using Inertial Measurement Unit towards Kendo Skill Improvement Support System

Abstract: In the field of sports, there are increasing opportunities to use inertial measurement units (IMUs) to enhance the training process and improve the performance of athletes. We focus on kendo, a traditional martial art using shinai (bamboo swords) in Japan, and propose methods for detecting and recognizing strike activities using IMUs towards realizing a kendo skill improvement support system. We used a sensor data set of strike activities obtained from 14 participants (seven kendo-experienced and seven inexper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Here, the sampling rate is 100 Hz. In this study, data preprocessing and feature extraction are performed in accordance with the findings of existing studies; (10,15) we apply a sliding window with a window size of 1.28 s (1 window = 128 samples) and a step size of 0.64 s. We first apply a noise reduction process to nine different time-series data using a 0.3 s median filter. Next, we separate the sensor data into time-domain and frequency-domain series using a Fast Fourier transform.…”
Section: Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the sampling rate is 100 Hz. In this study, data preprocessing and feature extraction are performed in accordance with the findings of existing studies; (10,15) we apply a sliding window with a window size of 1.28 s (1 window = 128 samples) and a step size of 0.64 s. We first apply a noise reduction process to nine different time-series data using a 0.3 s median filter. Next, we separate the sensor data into time-domain and frequency-domain series using a Fast Fourier transform.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…They analyzed inertial sensor data of striking motions of experienced and inexperienced kendo players and reported that the proposed method based on dynamic-time warping could detect striking motions with an F value of 89.9%. (10) Blank et al attached inertial sensors to table tennis rackets and collected data on eight basic stroke types from 10 amateur and 10 professional players. First, a single stroke was detected using an event detection algorithm.…”
Section: Related Workmentioning
confidence: 99%
“…In order to apply time-related features, each data type is divided by a fixed-length window. In our system, we selected a window size of 1.24 seconds [4], [26], which is commonly used in accelerometer activity recognition. The window overlap rate is 50%.…”
Section: B Lifelog Generation Blockmentioning
confidence: 99%
“…2) Feature extraction: Since time-series data are the target of this study, we use the following 17 features that have been validated in previous studies [4], [26] related to activity recognition using accelerometers: mean, standard deviation, median absolute deviation, maximum, minimum, sum of squares, entropy, interquartile range, fourth-order Burg autoregressive model coefficients, range of minimum and maximum values, root mean square, frequency signal skewness, frequency signal kurtosis, maximum frequency component, frequency signal weighted average, frequency band spectral energy, and power spectral density.…”
Section: B Lifelog Generation Blockmentioning
confidence: 99%